ANALYSIS OF LEARNING EFFECTIVENESS USING THE DEEP LEARNING APPROACH IN ELEMENTARY SCHOOLS - Hidayat, A. Gafar; Haryati, Tati (Kurikula : Jurnal Pendidikan, 2025)
The purpose of this study is to describe the effectiveness, readiness and suitability of the learning approach framework using the deep learning approach in elementary schools, especially the readiness of resources, both teachers and supporting facilities for learning activities in elementary schools in Bima. The method used in this study is library research, by systematically reviewing literature to collect, evaluate, and synthesize information from various sources relevant to the research topic. The study result indicate that the deep learning approach in learning consists of 3 main pillars, namely understanding the differentiation of student learning, inviting students to think critically in solving problems, and learning with fun, so that students can easily remember what has been learned. The application of deep learning in elementary schools emphasizes contextual learning that can be applied to learning science, mathematics, Indonesian, PPKn, PAI, and other non-curricular learning. It's just that this approach can be. Applied chose the synonim if the teacher is able to contextualize the latest issues, with the subject matter delivered. For teachers who have participated in the school mover program or teacher practice/movers, they can easily apply and combine deep learning as a learning approach, but in one elementary school not all teachers follow the program. This means that there needs to be mentoring or training from driving teachers or GMP group groups and the like, for all elementary school teachers, and this does not rule out the possibility of being implemented well, as a deep, detailed and enjoyable learning approach.